The Cavaliero Pasquil: An Anti-Marprelate Persona - Hill, Chris (Christianity & literature, 2023)
Broadly considered, the popular pamphlets written against Martin Marprelate in the months encompassing 1589–1591 are treated as pale imitations of their adversary, whose rhetorical and argumentative virtuosity earned him great notoriety. Considered as strenuous attempts to both counter Martinist aggression and also solve the rhetorical problems he presented, the aggressive Pasquil tracts (1589–1590) reveal how the adoption of an established satirical persona and mode allows a writer defending the Elizabethan bishops to both adopt and condemn the dangerous speech marking the Marprelate program. The tracts thus exhibit the self-generative and popular appeal characteristic of early print and pamphlet culture.